2021
DOI: 10.3390/ph14040371
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, Biological Evaluation and In Silico Studies of Pyrazole-Based NH2-Acyl Oseltamivir Analogues as Potent Neuraminidase Inhibitors

Abstract: Oseltamivir represents one of the most successful neuraminidase (NA) inhibitors in the current anti-influenza therapy. The 150-cavity of NA was identified as an additional binding pocket, and novel NA inhibitors have been designed to occupy the 150-cavity based on the structure information of oseltamivir carboxylate (OC) in complex with NA. In this study, a series of C-5-NH2-acyl derivatives of OC containing the pyrazole moiety were synthesized. Several derivatives exhibited substantial inhibitory activity aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Finally, four compounds, J098-0498, 1067-0401, M013-0558, and F186-0261 displayed acceptable parameters in the ADME/T calculation (Figure 7). The values of the Qikprop descriptors for the four hit compounds were depicted in Table 6 and all of them fell in the standard range of parameters [49,50]. The aqueous solubility (QPlogS) of these compounds was predicted satisfactory and the percentages of oral absorption very high (80%).…”
Section: D Qsar Auto Qsar and Adme/t Predictionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, four compounds, J098-0498, 1067-0401, M013-0558, and F186-0261 displayed acceptable parameters in the ADME/T calculation (Figure 7). The values of the Qikprop descriptors for the four hit compounds were depicted in Table 6 and all of them fell in the standard range of parameters [49,50]. The aqueous solubility (QPlogS) of these compounds was predicted satisfactory and the percentages of oral absorption very high (80%).…”
Section: D Qsar Auto Qsar and Adme/t Predictionmentioning
confidence: 99%
“…Results revealed that all the molecules were druggable without any violation of Lipinski's rule of five (Table S2). The values of the Qikprop descriptors for the four hit compounds were depicted in Table 6 and all of them fell in the standard range of parameters [49,50]. The aqueous solubility (QPlogS) of these compounds was predicted satisfactory and the percentages of oral absorption very high (>80%).…”
Section: D Qsar Auto Qsar and Adme/t Predictionmentioning
confidence: 99%